Optimization of Pb (II) Ion Removal from Synthetic Wastewater Using Dead (Chlorophyta) Macroalgae: Prediction by RSM Method - Dawood, Daad S.; Alwared, Abeer I.; Alkhazraji, Sara S.; Abdul-Majeed, Wameath S. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
The Pb2+ ions biosorption removal onto dead biomass of Chlorophyta algae is optimized by employing response surface methodology (RSM). Central composite design (CCD)-based experiments were carried out, and RSM was used to evaluate the results. The effects of contact time (15-120min), with pH solution (2-7), initial lead concentration (25-100 mg/L), biomass dose (0.01-1 g/100 mL), agitation speed (100-300 rpm) on the biosorption process were investigated. The optimal conditions of the experimental, data were pH (5), metal concentration (50mg/L), dosage (0.2g/100mL), agitation speed (200 rpm), and contact time of 120 min with constant particle size (63 mm), which gave 98.88% removal efficiency. All the variables and reactions in the biosorption experiments were evaluated using the desirability function to determine the optimal point at which the desired parameters may be attained. The promising results obtained indicate the potential use of Chlorphyta green macroalgae to treat industrial wastewater polluted with toxic metals.